Pendampingan Penerapan Standar Akuntansi Keuangan EMKM Dalam Penyajian Laporan Keuangan UMKM Sebagai Salah Satu Dasar Pengajuan Kredit Pinjaman Bank - Krismayanti, Elsa; Marlina, Tri; Yuliandi, Yuliandi (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
In the economy of Indonesia, micro small and medium enterprises are the business sectors most undertaken by the people of Indonesia. SMES is one of the nation's economic drivers because it is able to create greater growth and absorption of manpower so as to encourage the national economic growth continuously. Micro, small, and medium enterprises have an important role in economic growth and its existence is able to directly impact the lives of middle to lower society. This research aims to provide information on the report of the statement to Msme-based financial Accounting standards entity, micro, small and medium (SAK emkm) can also be applied by SMEs in drafting the report of the statement. Karen with financial reports can know the financial position and performance of the company. The object of this research is SMES CV Rafila. The research methods used in this study are qualitative descriptive methods. This research is elaborated in detail regarding the stages of drafting financial statements. The results showed that SMES CV Rafila does not yet have a financial report corresponding to the accounting standards entity, micro, small, and medium. MSME CV Rafila only make the registration of financial very simple and do not use financial statements as a basis to obtain additional capital from the funding/bank. Keywords : SMES, financial report, SAK EMKM.